Dinamika Aliran Lahar dengan Model Dua Fluida pada Topografi Kompleks - HAMDAN, Abdul Mujahid ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia is part of the territory through which the ring of fire that causes many volcanoes on its region. Disaster lahar flow is one of the secondary hazards of volcanic eruptions. Therefore, it is very important to study the behavior of its flow, as the efforts of prevention and risk reduction. Previous theory and models have not explain the effect of curvature and torsion topography of two-fluid model flow. The model on this research constructed with theoretical studies using mathematical analytical method to obtain the triangular and rectangular cross section of thick flow, as well lahar flow dynamics model with two-fluid model of the topography involving curvature and or torsion of shallow flow. The experimental results show the relationship between the carrying capacity of the volume fraction of water, the slope down of the plane and difference between granular and fluid velocity is linear, whereas the relationship between the carrying capacity with the volume fraction of granular is inversely. The analysis result show that be required to introduc a number called the carrying capacity number.